Sensing a rainbow of colors: algal photoreceptors - Hallmann, Armin (Frontiers in Plant Science, 2025)
Algae inhabit diverse environments with highly variable light conditions, making light sensing essential for survival and ecological success. This review explores the remarkable diversity of algal photoreceptors, enabling detection and response to a broad spectrum of sunlight, from ultraviolet to far-red wavelengths. Algae utilize various light-sensitive proteins—including flavin-based receptors (phototropins, cryptochromes, aureochromes, BLUF proteins), retinal-based rhodopsins, tetrapyrrole-based phytochromes, hybrid neochromes, and UV-B photoreceptors — to sense and integrate both light quality and quantity. The evolution of these photoreceptors has been shaped by endosymbiotic events, gene duplication, and domain fusion, equipping algae with robust mechanisms for environmental adaptation. Advances in genomics and transcriptomics have revealed many novel algal photoreceptors, some of which are being harnessed as optogenetic tools in biomedical research. Channelrhodopsins from green algae, for example, have revolutionized neuroscience by enabling precise, light-controlled manipulation of neuronal activity. The ongoing discovery and engineering of algal photoreceptors continue to expand the molecular toolkit for both basic research and practical applications. In summary, algal photoreceptors exemplify evolutionary innovation in adapting to diverse light environments and underpin numerous physiological processes critical for algal survival. Study and exploitation of these proteins offer profound insights into light perception, signaling, and technological applications, particularly in the rapidly growing field of optogenetics.